Determination of Extravasation Effects of Nal-Iri and Trabectedin and Evaluation of Treatment Options for Trabectedin Extravasation in a Preclinical Animal Model - Keritam, Omar; Juhasz, Viktoria; Schöfer, Christian; Thallinger, Christiane; Aretin, Marie-Bernadette; Schabbauer, Gernot; Breuss, Johannes; Unseld, Matthias; Uhrin, Pavel (Frontiers in Pharmacology, 2022)
Background: Extravasation during chemotherapy administration can lead to dangerous adverse effects ranging from pain to tissue necrosis. Evidence-based data about prevention and treatment of extravasation injuries of some clinically used compounds still remains elusive. This work aimed to investigate, in a preclinical mouse model, the effects of extravasation of two chemotherapeutic agents, nanoliposomal irinotecan (nal-Iri) and trabectedin. In addition, we aimed to study treatment options for injuries induced by extravasation of these substances. Methods: Mice were subcutaneously injected with nal-Iri or trabectedin applied in clinically used concentration. Doxorubicin was used as a positive control. In subsequently performed experiments, hyaluronidase, DMSO and tacrolimus were tested as potential treatments against extravasation-induced injuries by trabectedin. Systemic effects were analyzed by observation and documentation of the health status of mice and local reactions were measured and graded. In addition, hematoxylin-eosin stained histological sections of the treated skin areas were analyzed. Results: Of the two tested substances, only trabectedin showed vesicant effects. Subcutaneous injection of trabectedin caused erythema formation in mice by day two that was progressing to skin ulcerations by day five. Furthermore, we found that topical treatment of mice with tacrolimus or DMSO reduced the vesicant effects of trabectedin. The results observed in vivo were supported microscopically by the analysis of histological sections. Conclusions: We recommend classifying trabectedin as a vesicant agent and nal-Iri as a non-vesicant agent. Furthermore, our results obtained in a preclinical model suggest that tacrolimus and DMSO might be suitable treatment options of trabectedin extravasations, a finding that might be further utilized in clinical studies.